An Unusual Localization of Lunate in a Transcaphoid Volar Lunate Dislocation: Current Concepts - Grigorios Kastanis; George Velivasakis; Anna Pantouvaki; Manolis Spyrantis (Case Reports in Orthopedics)
Perilunate dislocation and fracture dislocations are rare injuries corresponding to 10% of all carpal injuries. They usually come with high-energy trauma, with associated injuries representing 61%. Volar lunate dislocation or fracture-dislocation accounts for 3% of perilunate injuries. We present a case of a 42-year-old polytrauma male, transmitted to our department 48 hours after a car accident with a trans-scaphoid volar lunate dislocation. During operation, the lunate was displaced volarly to the ulnar side of the wrist, forward to the styloid process of the distal ulna, while the scaphoid fracture appeared at the waist with comminution, and the proximal pole of the scaphoid protruded under the dorsal capsule. Carpal injuries are often missed out in polytrauma patients, and these injuries are underestimated because of the severity of the other visceral or extremity lesions. Untreated or improperly treated, those injuries lead to serious morbidity and loss of function. Therefore, good functional prognosis with decreased percentage of complications can be achieved following early recognition and early open surgical ligamentous complex repair.